2012
DOI: 10.1371/journal.pone.0029666
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Mitoferrin Results in Abnormal Development and Extended Lifespan in Caenorhabditis elegans

Abstract: Iron is essential for organisms. It is mainly utilized in mitochondria for biosynthesis of iron-sulfur clusters, hemes and other cofactors. Mitoferrin 1 and mitoferrin 2, two homologues proteins belonging to the mitochondrial solute carrier family, are required for iron delivery into mitochondria. Mitoferrin 1 is highly expressed in developing erythrocytes which consume a large amount of iron during hemoglobinization. Mitoferrin 2 is ubiquitously expressed, whose functions are less known. Zebrafish with mitofe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Iron accumulation in mitochondria and increased mitochondrial oxidative damage have been observed as a function of age (Atamna, 2004;Mallikarjun et al, 2014;Seo et al, 2008), although no evidence for the participation of mitoferrin has been demonstrated. In contrast, treatment of Caenorhabditis elegans with RNA interference for mitoferrin results in a 50-80% increase in lifespan, accompanied by decreased body size and reduced fecundity (Ren et al, 2012). These results indicate the importance of mitochondrial iron accumulation during aging and the possible participation of mitoferrin-2 in this process.…”
Section: Mitoferrinmentioning
confidence: 88%
“…Iron accumulation in mitochondria and increased mitochondrial oxidative damage have been observed as a function of age (Atamna, 2004;Mallikarjun et al, 2014;Seo et al, 2008), although no evidence for the participation of mitoferrin has been demonstrated. In contrast, treatment of Caenorhabditis elegans with RNA interference for mitoferrin results in a 50-80% increase in lifespan, accompanied by decreased body size and reduced fecundity (Ren et al, 2012). These results indicate the importance of mitochondrial iron accumulation during aging and the possible participation of mitoferrin-2 in this process.…”
Section: Mitoferrinmentioning
confidence: 88%
“…Mitochondrial transporters with homology to S. cerevisiae Mrs3 and Mrs3 are widespread in eukaryotes and their crucial function in mitochondrial iron supply has been documented for fungi (Nyhus et al, 2002), zebrafish (Shaw et al, 2006); plants (Bashir et al, 2011), C. elegans (Ren et al, 2012), Drosophila (Metzendorf et al, 2009) and mammals (Bashir et al, 2011;Paradkar et al, 2009). They are members of the mitochondrial solute carrier family (MCF, or human SLC25), a large group of structurally related integral proteins of the inner mitochondrial membrane that catalyze the exchange of water-soluble metabolites, including nucleotides, inorganic ions and vitamins across the mitochondrial inner membrane (Arco and Satrustegui, 2005;Gutierrez-Aguilar and Baines, 2013;Kunji and Robinson, 2006;Palmieri, 2008).…”
Section: The Mitochondrial Inner Membrane Transportersmentioning
confidence: 99%
“…SLC25A37 provides a critical role of iron-consuming processes including heme synthesis and Fe-S cluster synthesis in mitochondria [45,49]. Over expression of SLC25A37 and increased mitoferron-1 protein lead to increased iron uptake into mitochondria and promotes heme synthesis [45], and this increased matrix free iron potentially can increase hydroxyl radical formation from hydrogen peroxide [46]. Moreover, iron overload affects the mitochondrial calcium uniporter, slow calcium uptakes, and results in mitochondrial dysfunction [50], which may intensify fatigue experienced by men treated with XRT.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, up-regulation of SLC25A37 increases the mitochondrial inner membrane mitoferrin-1 protein [44]. Increased mitoferrin-1 protein leads to increased iron uptake into mitochondria and promotes heme synthesis [45], and this increased matrix free iron potentially can increase hydroxyl radical formation from hydrogen peroxide [46].…”
Section: Introductionmentioning
confidence: 99%